Melatonin protects against myocardial doxorubicin toxicity in rats: role of physiological concentrations - Sahna, E; Parlakpinar, H; Ozer, MK; Ozturk, F; Ozugurlu, F; Acet, A (Wiley, 2003)
Doxorubicin (Dox) is a widely used antineoplastic drug. Oxygen radical-induced injury of membrane lipids is considered to be the most important factor responsible for the development of Dox-induced cardiotoxicity. The pineal secretory product, melatonin, is known to be a potent free radical scavenger and its pharmacological concentrations have been shown to reduce Dox-induced cardiac damage. However, the physiological role of melatonin in the prevention of this damage is unknown. We investigated physiological and pharmacological effects of melatonin on Dox-induced changes in the levels of malondialdehyde (MDA), a lipid peroxidation product, and morphological changes in heart. Rats were pinealectomized (Px) or sham-operated ( control) 2 months before the studies. Melatonin was administered [ 4 mg/kg, intraperitoneally (i.p.)] 1 hr before or 24 hr after the administration of a single dose of Dox ( 20 mg/kg, i.p.) and continued for 2 days. The levels of MDA Dox was found to be significantly higher in the Px rats (55.9 +/- 0.6 nmol/g tissue) than intact control animals (42.6 +/- 0.4). Dox administration to Px and non-Px rats significantly increased the MDA levels. Pre- and post-treatment with melatonin in both Px and intact rats significantly reduced MDA levels. Morphological changes parallelled the MDA alterations. These findings strongly suggest that both physiological and pharmacological concentrations of melatonin are important in protecting the heart from Dox-induced damage in rats. It would seem valuable to test melatonin in clinical trials for prevention of possible heart damage associated with Dox.
Keywords: doxorubicin; heart; melatonin; pinealectomy; rats